Forensic Findings in Exhumation Cases in North Sulawesi in 2019-2020 - Aurelie B. Kasenda; Erwin G. Kristanto; Nola T. S. Mallo (e-CliniC, 2022)
Abstract: Exhumation is a procedure of removing a corpse carried out for medicolegal investi-gations, relocation, or other purposes. This study aimed to determine the overview of forensic findings in exhumation cases in North Sulawesi during the years 2019-2021. This was a descriptive and retrospective study using data of Visum et Repertum. The results obtained five cases of exhumation during the period of January 2019-August 2021. In year 2019 there was the most frequent exhumation performed, namely three cases (60%). Based on sex, three (60%) corpses were female. In 80% of the cases, the cause of death could still be determined, while in 20% of cases could not be determined anymore. Age was dominated by the adult age group, namely 26-45 year olds. The pattern of the wounds found were blisters, bruises, and lacerations with the same number and the most common location was in the head area. In conclusion, most of the forensic findings in exhumation cases in North Sulawesi registered at Prof. Dr. R. D. Kandou Hospital Manado year 2019-2021 could reveal the most common cause of death, namely blunt force trauma with bruises, abrasions, as well as lacerations, and head as the most common site of injury.Keywords: exhumation; forensic findingsÂ Abstrak: Ekshumasi merupakan prosedur penggalian jenazah yang dilakukan untuk kepentingan investigasi medikolegal, relokasi, ataupun tujuan lainnya. Penelitian ini bertujuan untuk mengetahui gambaran temuan forensik pada kasus ekshumasi di Sulawesi Utara tahun 2019-2021. Jenis penelitian ialah deskriptif retrospektif dengan menggunakan Visum et Repertum. Hasil penelitian mendapatkan lima kasus ekshumasi selama periode Januari 2019-Agustus 2021. Tahun 2019 merupakan tahun dengan kasus ekshumasi terbanyak yaitu sebanyak tiga kasus (60%). Jenis kelamin paling banyak ialah jenazah perempuan dengan jumlah tiga kasus (60%). Pada 80% kasus ekshumasi dapat ditentukan sebab kematiannya, sedangkan pada 20% tidak dapat ditentukan lagi. Usia didominasi oleh kelompok usia dewasa yaitu 26-45 tahun. Pola luka yang ditemukan ialah luka lecet, luka memar, dan luka robek dengan jumlah yang sama serta lokasi terbanyak ditemukan ialah pada daerah kepala. Simpulan penelitian ini ialah sebagian besar temuan forensik pada kasus ekshumasi di Sulawesi Utara yang tercatat di RSUP Prof. Dr. R. D. Kandou tahun 2019-2021 dapat mengungkapkan sebab kematian, yang terbanyak yaitu kekerasan tumpul dengan jumlah luka memar, lecet, dan robek yang sama serta lokasi cedera tersering pada kepala.Kata kunci: ekshumasi; temuan forensik